MOTIVASI PETANI MEMBUDIDAYAKAN TANAMAN OBAT DI KECAMATAN ,JUMAPOLO KABUPATEN K.ARANGANYAR - Widiyanto Widiyanto (AGRITEXTS: Journal of Agricultural Extension, 2005)
Jumapolo Subdistrict is area of Development Superior Commodities Agricultural Center of herbal medicine specially "emponempon ". This is influenced by motivations encourage farmers. Motivation is o good encouragement that comes form inside or outside individually or grouply. This Motivations encourage farmers to cultivate"}edicine plants. The elements of motivation are important for herbal medicine cultivation. Thus, the goals of this research is identify of motivation elements. From the result showed that farmer's motivation in herbar medicine cultivation was medium. The economical motivation was low and biological motivation motivation was more lower while the other factors psychological and sociological were higher.